A CASE STUDY OF ENGINEERING ETHICS: LESSON LEARNED FROM BUILDING COLLAPSE DISASTER TOWARD MALAYSIAN ENGINEERS - Sulaima, Mohamad Fani; Lew, H. S.; Lau, C. Y.; Lim, Carolyn K. Y.; Azily, Ahmad Tarmizi (Center for Enhancing Knowledge (CEK), UK, 2014)
This paper presents the case study on the Hotel New World tragedy. The building collapsed on 15th March 1986 and an investigation was conducted to determine the main cause of this tragedy. There were several speculations made on the cause of the collapse such as internal explosion, bad concrete mixture and swampy land affecting the building’s foundations. However, after thorough investigations, these speculations were proved to be inappropriate and the main cause was found to be due to the engineer’s miscalculation during the designing stage which leads to this catastrophic failure of the building. Rescue operation was initiated immediately after the collapse to rescue the victims and the aftermath of this tragedy had led to multiple reclamations. These reclamations include the endorsement of Building Control Act 1989 along Building Control (Accredited Checkers) Regulations 1989 as a stricter quality control measure. The analysis shows that this case may be due to unwanted mistakes or negligence of the engineers in carrying out their duties. Several actions were taken according to the ethical theories and codes of ethics. However after the analysis and evaluation were done, duty ethics and right ethics were more relevant to the collapse of Hotel New World case as compared to the other ethical theories and thus reclamations were done based on duty ethics and right ethics